Driver’s Visual Engagement in Urban Streetscape - Lanta Kautsar Akromi; Bambang Soemardiono; Purwanita Setijanti (IPTEK Journal of Proceedings Series, 2020)
Representation of visual engagement in urban street through the streetscape is an important in urban design research as a city framework. Urban street are composed of various classifications and attract more attention from townspeople. Visual engagement is an important component for understanding a city. Human's perception of the nature environment and build environment gives a difference feeling to the visual. The city formed by many urban street that forms it. However, the establishment of this street still does not pay attention to the interests about visual on the street system as a city frameworks, but only pay attention to the function of the street. Urban street have regulations related to speed limits that are affect the visual of the driver. The importance of visual engagement driver’s when through the street to understanding of the city. The methodology in this study uses a post-positivist paradigm with quantitative strategies. Data collection tactics using Likert scale questionnaires was given to drivers or people who through the street by car with intensity once a week and data analysis uses SPSS application with descriptive statistics to identify factors that the most affect. The results of this study are to identify the factors of the urban streetscape that the most affect to the drivers when through the street. The visual elements factor that include the mass of the building, building entrance, textures, colours, and materials was establish the enclosure space on the street corridor. from these results identified a new factors that affect to visual engagement drivers.